2017
DOI: 10.1177/2167702617743002
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Safety Signal: Social-Support Figures Enhance Rather Than Protect From Fear Extinction

Abstract: Although research has made significant advances in identifying treatments for fear-related disorders, these treatments are not entirely effective and relief from symptoms is often short-lived (Craske, 1999; McNally, 2007; Rachman, 1989). The research on which these treatments are based has largely focused on investigating processes by which fears are learned with an eye toward enhancing fear extinction. Less work, however, has examined safety stimuli (which denote the absence of threat) and whether specific ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 22 publications
2
43
2
1
Order By: Relevance
“…This suggests a powerful and lasting inhibitory effect of social-support figures on the fear response. This enhanced extinction effect was replicated immediately postextinction as well as 24 hr postextinction (Hornstein, Haltom, Shirole, & Eisenberger, 2017; Fig. 2b).…”
Section: The Effect Of Social-support Figures On Fear Acquisition Andmentioning
confidence: 68%
See 1 more Smart Citation
“…This suggests a powerful and lasting inhibitory effect of social-support figures on the fear response. This enhanced extinction effect was replicated immediately postextinction as well as 24 hr postextinction (Hornstein, Haltom, Shirole, & Eisenberger, 2017; Fig. 2b).…”
Section: The Effect Of Social-support Figures On Fear Acquisition Andmentioning
confidence: 68%
“…In both graphs, error bars indicate ±1 SE . Graphs were modified from (a) Hornstein and Eisenberger (2017) and (b) Hornstein, Haltom, Shirole, and Eisenberger (2017).…”
Section: The Effect Of Social-support Figures On Fear Acquisition Andmentioning
confidence: 99%
“…Eisenberger et al ( 2011 ) recently investigated the face of an attachment figure as inhibitor of stress-related responses in studies on pain perception and fear learning (Hornstein et al, 2016 , 2018 ; Hornstein and Eisenberger, 2017 ). Using a passive picture viewing procedure within an fMRI scanner, female participants received painful thermal stimulation of two intensities (moderate and high) at regular intervals while viewing pictures of their romantic partner or of a stranger or object.…”
Section: Psychobiological Mechanisms Underlying the Association Between Social Support And Longevitymentioning
confidence: 99%
“…Studies by Eisenberger on social support figures during fear learning used a Pavlovian shock conditioning procedure to condition the skin conductance response to faces of social support figures (“ the two individuals that give you the most social support on a daily basis ”) in comparison to faces of strangers or known people or neutral objects. The results obtained demonstrate that in comparison to faces of strangers and neutral objects, social support faces, either presented alone or paired with control faces, act as safety signals with the following capacities: (a) to inhibit their own fear conditioning (Hornstein et al, 2016 ), (b) to inhibit the expression of fear toward previously conditioned stimuli (Hornstein et al, 2016 ), (c) to inhibit the fear conditioning of new stimuli (Hornstein and Eisenberger, 2017 ), and (d) to enhance the extinction of conditioned fear responses and prevent the return of fear after a fear reinstatement procedure with additional shocks (Hornstein et al, 2018 ). Based on this evidence, Eisenberger and colleagues suggested that social support figures have become biologically prepared safety stimuli, analogous to biologically prepared fear stimuli (Seligman, 1971 ; Öhman, 1986 ), because over the course of evolutionary history they have provided individuals with protection, care, and resources, which has ultimately promoted survival (Hornstein et al, 2016 , p. 1,051).…”
Section: Psychobiological Mechanisms Underlying the Association Between Social Support And Longevitymentioning
confidence: 99%
“…Yet, surprisingly, recent work has demonstrated that while social support reminders do in fact inhibit fear responding [ 6 ] like safety signals, they have the additional effect of enhancing fear extinction [ 6 – 8 ], in contrast to safety signals. Indeed, while safety signals prevent any long-term reduction in fear responding, social support reminders lead to fear reduction that lasts longer than if fear extinction is conducted in the presence of images of neutral objects [ 6 ], images of strangers [ 6 , 7 ], or pretrained safety signals [ 8 ], with no return of fear following extinction procedures or even 24-hours-later following a test designed to reinstate fear (please see Figure 1 ). This distinct and never-before-seen combination of effects suggests that social support reminders are not engaging the same mechanisms as safety signals during fear learning processes and thus should not be assumed to belong in the safety category.…”
Section: Evidence For the Beneficial Role Of Social Support Reminders During Fear Extinctionmentioning
confidence: 99%